A review on the renewable energy from agricultural and forest residues in nigeria (2021)
Nigeria is blessed with abundant natural resources among them are residues from agricultural and forest sources. Since these residues are usually dumped in landfills as waste, constituting environmental and waste disposal problems, the need to utilise them is necessary in achieving the seventh and ninth targets of the Sustainable Development Goals (SDGs) of the United Nations. One of the avenues where agricultural and forest residues can be utilised is through biomass technology. Therefore, this paper assessed the potential conversion of these residues into useful and sustainable electricity generation in Nigeria. In addition, the paper gathers information from a pool of relevant reports on the current state of Nigeria’s power sector and the domestication of some small-scale biomass power plants across the country. In this review paper, it was found that Nigeria is one of the biggest economic power in Africa and has the potential to generate electricity and other bioenergy products from the present stock of biomass available in the country, thereby making the country self-sufficient in the provision of power supply and fuel production.